Impact of maternal obesity and diabetes on fetal pancreatic development - Nielsen, Jens H.; Jaksch, Caroline; Iessi, Isabela [UNESP]; Damasceno, Débora C. [UNESP] (Taylor & Francis, 2017)
The global epidemics of obesity and type 2 diabetes (T2D) are serious threats to human health and health-care expenses. Although genetics is an important factor, it does not explain this dramatic increase that involves environmental factors such as nutrients, gut microbiota, and lifestyles. Twenty-five years ago, the concept of “fetal programming” or “Developmental Origins of Health and Disease” was introduced stating that the intrauterine environment during pregnancy has an impact on gene expression that may persist through adulthood and be transmitted to the next generations. It was found that both under and overnutrition before and during pregnancy may cause metabolic diseases like obesity and T2D. Studies in humans have shown that offspring of mothers with obesity, type 1 diabetes (T1D), T2D, or gestational diabetes mellitus (GDM) are prone to develop metabolic disorders such as obesity, T2D, and GDM in adult life (Carrapato 2003; Hummel et al. 2013; Ruchat et al. 2013; Yan and Yang 2014). In certain populations, up to 15% of pregnant women develop GDM (King 1998) and offspring of GDM mothers has an up to eightfold increased risk of developing T2D or 126prediabetes later in life (Clausen et al. 2008). Obesity is a risk factor for development of GDM (Black et al. 2013; Fox et al. 2014), and the prevalence of obesity in women of reproductive age (20-44 years) in the United States is around 33% (Huda et al. 2010). Among pregnant women in 20 U.S. states, 20.5% were prepregnant obese in 2009 (Fisher et al. 2013). The clinical consequences of obesity and diabetes in pregnancy for the offspring will be dealt with in Chapters 13 and 14 of this book.